Genetica, citogenetica y mejoramiento de la yuca - Acosta E., J. (International Center for Tropical Agriculture, 1991)
Important aspects related to the genetics and cytogenetics of cassava are reviewed. One of the most appropriate techniques for genetic recombination in cassava is polycrossing; breeding methods most commonly used are clonal selection and directed crossbreeding. Indications are also given of floral structure, flowering habit, and pollination of the cassava plant. The most promising breeding methods to obtain desirable genotypes are reviewed, namely improvement of plant populations either within populations (selection between and within families of half-siblings or full- siblings, recurrent selection) or between populations and interspecific hybridization. Some nonconventional breeding methods such as the induction of mutations and tissue culture are indicated. (CIAT)